Convalescent Plasma Therapy for COVID-19 with Pregnancy in Sanglah Hospital, Denpasar - Ni Luh Ayu Suwandari; Ni Kadek Mulyantari; Ida Ayu Putri Wirawati (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
The Coronavirus Disease 2019 (COVID-19) was declared a pandemic by the World Health Organization (WHO). Pregnant females are a vulnerable population to contract COVID-19. The most promising therapies for COVID-19 infection are Remdesivir and Convalescent Plasma Therapy (CPT). Convalescent plasma therapy in COVID-19 with pregnancy is rare. A 26-year-old female with 29-30 weeks pregnancy with complaints of shortness of breath and cough was referred. Physical examination showed an increase in respiratory rate. Laboratory tests showed increased WBC (leukocytosis), anemia, thrombocytosis, Neutrophil-Lymphocyte Ratio (NLR), SGOT, and C-reactive protein. The results of the RT-PCR molecular biology test showed confirmed COVID-19. In treatment, complaints worsened with a respiratory rate of 32 beats/minute and oxygen saturation of 93%. The patient was treated with CPT and showed clinical improvement. Convalescent plasma therapy in pregnancy with COVID-19 aims to prevent the binding of spike protein (S) in the virus with the ACE-2 receptor in the host. Convalescent plasma therapy should be carried out in the right conditions according to the agreed criteria. Because clinical and laboratory improvements were observed in this study after convalescent plasma therapy was administered, it can be considered as an alternative therapy in severe clinical conditions.